Germ‐free mice as a model to study effect of gut microbiota on host physiology. Issue 6 (June 2014) - Grover, M.; Kashyap, P. C.
Abstract The alterations in resident gut microbiota seen in chronic gastrointestinal disorders have led to an increasing interest in the role of gut bacteria in maintaining intestinal barrier function. While acute alterations in colonic secretomotor function in response to pathogens have been well described, the effect of commensal bacteria on intestinal barrier function and colonic secretomotor function still remains poorly understood. Germ‐free mice represent a model system to study effect of gut microbes on host gastrointestinal physiology. The study by Lomasney et al. represents an important step in this direction by demonstrating that the colonic secretomotor function is largely preserved in germ‐free mice, hence making them a suitable model to study effect of gut microbiota on host function.